Analisis Pengaruh Nilai Tukar Rupiah Terhadap Pembandingan Penggunaan Kina Di Kampung Mosso Muara Tami Papua - Alius Almung; Fransina W. Ballo; Novi Theresia Kiak (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to determine the influence of the rupiah exchange rate on the use of Kina in Mosso Village, Muara Tami, Papua. Quantitative methods were used in this research to analyze secondary data collected from the websites of Bank Indonesia and the Indonesian Central Bureau of Statistics. The number of quarters, which collects all information during the study period, was used for sampling. This research uses two independent variables: inflation, Bank Indonesia interest rates (SBI) and money supply (JUB). The dependent variable is the exchange rate. Multiple linear regression analysis, T test, and F test were used to analyze the data. The results of the T hypothesis test show that inflation has a significant influence on the exchange rate partially during the period studied, with a significance value of 0.001. The interest rate does not have a significant influence on the exchange rate partially during the period studied, with a significance value of 0.462. The money supply also does not have a significant influence on the exchange rate partially, with a significance value of 0.17. The results of the F hypothesis test with a significance value of 0.000 show that inflation, interest rates and money supply simultaneously have a significant influence on the exchange rate in the 2018–2022 period.